2004
DOI: 10.11150/kansenshogakuzasshi1970.78.398
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Rubella, Measles, Chickenpox, and Mumps in Nursing Students

Abstract: The past history of infection and vaccination, and serum antibodies against rubella, measles, chickenpox, and mumps were investigated, before vaccine was inoculated in the susceptible nursing students. The subjects were 221 nursing students (208 women, 13 men, the average age 18.4 +/- 1.8 years old) who entered Nagasaki University from 2001 to 2003. The positive rates of the past history of rubella, measles, chickenpox, and mumps were 49.8%, 28.1%, 86.4%, 50.7%, and that of previous vaccination were 31.7%, 69.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…Several authors investigated the immunity to childhood exanthematic diseases of healthcare workers [5][6][7][8][9][10] but few of medical or paramedical students [11][12][13]. The data are not all consistent with our ones.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Several authors investigated the immunity to childhood exanthematic diseases of healthcare workers [5][6][7][8][9][10] but few of medical or paramedical students [11][12][13]. The data are not all consistent with our ones.…”
Section: Discussioncontrasting
confidence: 44%
“…In brief, our results show high seroprevalence of positive antibodies against varicella and rubella, intermediate against measles, and low against mumps. The prevalence of positive antibodies to mumps and measles, in particular among subjects aged 25 years or less, is largely lower than other researches on healthcare workers [7,10] or medical and paramedical students [11,13]. Surprisingly, considering the possible serious involvement of reproductive system in mumps infection, males show a low prevalence of positive antibodies, especially when older than 25 years.…”
Section: Discussionmentioning
confidence: 73%
“…In one study, the reported rate of past history of mumps vaccination in students without antibodies was 85.0%, and in those with low-titre antibody students was 93.8% [16]. We found that the past history of mumps vaccination was reported at a rate of 14.5% and 85.7% were seropositive.…”
Section: Discussionmentioning
confidence: 84%
“…EIA is sufficiently sensitive and specific to evaluate immunity after natural VZV infection [3], and has frequently been used in serosurveillance [6][7][8][9][10][11]. In contrast, some experts in Japan have recommended IAHA for routine screening among HCPs because of its high sensitivity and low expense [12,13].…”
Section: Introductionmentioning
confidence: 99%